Tinjauan Hukum Pidana Islam dan Hukum Positif terhadap Kekuatan Pembuktian Saksi Ahli di Pengadilan - Afif Kurniawan Rafi’i; Fahmil Samiran (AHKAM, 2026)
The role of expert witnesses is a key element in the evidentiary system of criminal cases, both in positive criminal law and in Islamic criminal law; however, comparative studies that specifically analyze their position and evidentiary weight in these two legal systems remain limited. This study aims to analyze and compare the status and evidentiary strength of expert testimony in positive law and Islamic law, and to explain the extent to which expert testimony influences judicial conviction in deciding criminal cases. This research employs library research with a normative and comparative approach through an examination of statutory regulations, the Al-Qur’an, Hadis, legal literature, and relevant scholarly journals. The findings show that in positive law, expert testimony is recognized as a valid means of proof as regulated in Article 184 of the Criminal Procedure Code (KUHAP), but it is not absolutely binding because judges retain discretion to assess it based on their conviction and the adopted evidentiary system. Meanwhile, in Islamic law, expert testimony is positioned as part of qarinah or bayyinah that serves to assist judges in uncovering material truth, even though it does not stand alone as a primary means of proof. The study concludes that, despite conceptual and terminological differences, both legal systems place expert witnesses as supporting instruments of proof for realizing just decisions. The implications of this research provide theoretical and practical foundations for legal academics and practitioners in optimizing the role of expert witnesses in criminal proceedings in a more proportional and accountable manner.